New Keynesian and New Classical Debate on Contemporary Macroceconomic Development: Review - Mool, Bhumika (Journal of Economics Students, 2023)
This paper analyzes the extended debate between two schools of economic thought – Keynes and Classics with recently updated ideas noted as New Keynesianism (NK) and New Classicism (NC). Here, ideas on Keynesian and classical economics, their similarities, differences, successes, applicability and criticisms has been studied comparatively through descriptive analysis of previous articles from researchers and renowned economists since decades before. The paper suggests that the nomenclature issue between these macroeconomic developments is more than a terminological debate that points out what should be the current issue between Keynesians and Classicals. There are both similarities and differences within the schools of thoughts. The analysis shows the assumptions, criticisms and successes of two of these schools of economic thought viz. NC and NK and explains which of them is appropriate to be applied for assessing policy, monetarism and business cycle theory. Nevertheless, no matter how much they criticize and compete with one another or how many theories and explanations are added, their core remains the same while their applicability always differs in accordance to time and place.